Technology barriers and strategies in coordinating care for chronically ill patients. (July 2019) - Carayon, Pascale; Hundt, Ann Schoofs; Hoonakker, Peter
Abstract: Care managers who coordinate care for chronically ill patients in hospitals and outpatient settings use multiple health information technologies for accessing, processing, documenting, and communicating patient-related information. Using a combination of 41 interviews and observations of 15 care managers, we identified a range of technology-related barriers experienced by care managers (total of 163 occurrences). The barriers are related to (lack of) access to information, inadequate information, limited usefulness and usability of the technologies, challenges associated with using multiple health IT, and technical problems. In 43% of the occurrences, care managers describe strategies to deal with the technology barriers; these fit in three categories: nothing/delay (9 occurrences), work-arounds (32 occurrences), and direct action at the individual, team, and organization levels (29 occurrences). Our data show the adaptive capacity of care managers who develop various strategies to deal with technology barriers and are, therefore, able to care for chronically ill patients. This information can be used as input to work system redesigns. Highlights: Care managers frequently report technology barriers related to information (access and quality) and usability. About half of the time, care managers report strategies to deal with barriers. Information on barriers and strategies provides insights for work system redesign.